A hermeneutics of empathy: the artist interview in South Africa - Bosland, Joost Ooyke (My University, 2018)
This project consists of two parts: a selection of newly commissioned interviews with South African artists, titled Intent and Material: South African art in conversation, and a theoretical reflection on the significance of the artist interview in our local context, titled A Hermeneutics of Empathy: The artist interview in South Africa. Intent and Material contains interviews with Nicholas Hlobo, Zander Blom, Jody Maria Brand, Mikhael Subotzky, Bogosi Sekhukhuni and Ernest Cole. The accompanying thesis proposes the notion of a ‘hermeneutics of empathy’ as a way of thinking about artist interviews. This is a theoretical model, a wonderful phrase that draws together the work of N. Chabani Manganyi and Rita Felski, and suggests why the artist interview might be of interest in South Africa in 2018. At its best, an artist interview, through the push and pull between the two participants, reaches a level of thought about artistic practice that is rarely achieved in art criticism with a single author. The final, edited transcript has the potential to become an autonomous text that aides our understanding of an artist and the world they inhabit. Based on my reading of Manganyi and Felski, as well as Ronald Christ, Stacy Hardy and Ernest Mancoba, a new anthology of interviews with South African artists would be a meaningful contribution to local art criticism. It could achieve two separate but equally valuable goals: serve as an introduction to the local scene for curators and art historians from elsewhere, and contribute to a local literature on art that is of interest to non-specialists.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Fine Arts, 2018
Keywords: Artists--South Africa--Interviews; Arts, Modern--21st century; Artists--South Africa--Biography